General Introduction to the Works of Saint Bernard (II) - Leclercq, Jean (Cistercian studies quarterly, 2005)
Focuses on the art works of Saint Bernard. Miniatures, architecture and musical works of Saint Bernard; Literary works of Saint Bernard.